Mitigation of Distance-Dependent Errors for GPS Network Positioning - Musa, Tajul A; Lim, Samsung; Yan, Thomas; Rizos, Chris (IGNSS, Australia, 2006)
The effect of the atmosphere has been identified as the major problem of long-baseline carrier phase positioning. The effect of the ionosphere,however, can be neutralised with dual-frequency observations. Thus, the effect of the troposphere is the challenge of precise positioning and needs to be mitigated in some way. The network-based approach provides a non-dispersive correction that can be useful in reducing this effect. Applying the correction to the ionosphere-free combination improves the ambiguity resolution and hence guarantees higher accuracy. In addition, dispersive and non-dispersive corrections can be separately applied to the computation of the receiver position.